Using group work to improve teaching and learning quality for the students in the communal police chief class at the People’s security college I - Phạm, Thị Thu Ngà (University of Languages and International Studies, 2017)
It is widely admitted that teaching English in the Communal Police Chief class has a lot of disadvantages over other classes at the People‟s Security College I such as: students in the class are very crowded. They are different level. The class lacks of material foundation. However, teaching in a large multilevel class is a popular mode being used in most schools and universities in Vietnam. There exist many constraints on effective English teaching in such environment. When teaching as well as learning English in these classes, teachers and students have to face a lot of problems and difficulties. Thus, to improve this situation, I applied group work for teaching and learning four skills for the students in the CPC class at the PSCI.The paper then explores how to use group w ork of the teachers in the CPC classroomhandle their lessons to attract attention of the learners. On the basis of the brief analysis, a few suggestions, in the light of current education thinking to enhance classroom practice, are presented to see that skills teaching in the CPC class can be successful and students can develop their language skills